Oxidation of ethylene by Cu/TiO2: reducibility of Cu2+ in TiO2 as a possible descriptor of catalytic efficiency - Rajendran, K.; Sharma, Mandeep; Jaison, Augustine; Ankitha, Menon; Tiwari, Ankit D.; Vinod, C. P.; Jagadeesan, Dinesh (Catalysis Science & Technology, 2023)
Catalytic oxidation using non-noble metal-based catalysts is a promising approach to mitigate pollution due to VOCs in the air. In this work, mesoporous Cu/TiO2 catalysts containing different concentrations of Cu2+ (0.2, 1, 3, and 4 wt% Cu w.r.t. Ti) were synthesized using the sol-gel technique. The catalysts were characterized using inductively coupled plasma-optical emission spectrometry, XRD, Raman spectroscopy, N-2 physisorption, cyclic voltammetry, H-2-TPR and electron microscopy to understand the structure and composition. The thermal catalytic gas phase oxidation of ethylene was studied by heating a mixture of ethylene (1.5 vol%) and air (5.9 vol%) in the presence of the Cu/TiO2 samples in the temperature range of 298 to 773 K. Cu/TiO2 showed a higher catalytic activity compared to TiO2 for the thermal oxidation of ethylene, indicating a strong promotion by doped copper ions. A volcanic behaviour in the catalytic activity was observed with different concentrations of Cu doping, with 1% Cu/TiO2 showing a 99.5% ethylene conversion at 673 K and 100% selectivity to CO2. The activity of 1% Cu/TiO2 remained consistent without deactivation for 24 h. At low dopant concentrations of Cu (0.2 and 1% Cu/TiO2), the reduction of Cu2+ to Cu+ was observed. An interplay of oxygen vacancies (O-V), Cu+, Cu2+ and Ti4+ may be involved in controlling the activity. DRIFT studies indicated the formation of surface bidendate carbonate as a possible intermediate.